Explore activities management to support the care and education of public preschools - Pham, Thuan Van; Nguyen, LongAn Dang (Institute of Advanced Engineering and Science, 2025)
This study aims to explore the contents of the management of support activities for care and education, as well as the impacts of these activities on improving the quality of support and care for children in public preschools in Thu Duc city, Vietnam. To achieve this purpose, qualitative and quantitative research methods were used through the evaluation of relevant documents. At the same time, a survey of 175 people, including managers, teachers, and parents of students, was conducted. The research results show that although the management of support activities for care and education for children in public preschools has achieved some good results, it still reveals many limitations that need to be identified and addressed with appropriate solutions. Based on the assessment of the current situation and identification of the causes, this study has proposed suitable solutions to improve the quality of support activities for care and education for children in public schools in Thu Duc city.